Evaluasi kinerja karyawan wanita melalui konflik peran ganda dan gender - Monica Nur Aqmarina; Rachmatullaily Tinakartika Rinda; Jani . Subakti (University of Darussalam Gontor, 2020)
This research aims to evaluate the impact of female employee performance through multiple role and gender conflicts. The method used is a qualitative method with descriptive analysis and supported by previous journals related to variables accompanied by the use of in-depth interview techniques. The results of this study based on interviews and support theories and previous journals stated that there is an influence on performance through conflicts of dual roles and gender seen from how the imbalance of roles and beliefs is still minimal for female employees compared to men. Then to improve performance there needs to be motivation and sharing in exploring the potential to show women can be equally trusted by supporting women's empowerment in managing roles. So that, performance improvement can be accompanied by family harmony that is maintained and the trust of fellow colleagues. It can therefore be stated that there was an effect of performance through conflicts of dual roles and gender on the performance of female employees in the Regional Income Management Agency (BAPPENDA) bogor regency.